GAMBARAN DAN ANALISIS FAKTOR RISIKO GANGGUAN FUNGSI PARU PADA TENAGA KERJA PENGECAT SPRAY MOBIL DI DAERAH GATSU TIMUR DENPASAR, BALI - I Gede Bagus Bhaskara Wijaksana; I Made Muliarta (Universitas Udayana, 2015)
CHARACTERISTIC AND RISK FACTORS ANALYSIS FOR LUNG FUNCTION IMPAIRMENT AMONGST AUTOMOBILE SPRAY PAINT WORKERS IN GATSU TIMUR DENPASAR, BALIAutomobile spray paint industries are associated with high risk of occupational hazard. Spray paint workers are at high risk of isocynate exposure which has been associated with both obstructive and restrictive lung impairment. Risk factors such as duration of work, safety equipment, and history of smoking are among several risk factors involving lung function.The purpose of this study is to describe the lung function impairment among automobile spray paint workers in Gatsu Timur and analyze risk factors that influence them. Analytic cross- sectional method was used in this study. Subjects were 23 automobile spray paint workers in Gatsu Timur. Lung function impairment was measured using spirometer. The study showed that 60,8% of subjects have restrictive lung impairment and 17,3% have obstructive lung impairment. No significant relationship was found between duration of work, safety equipment, and history of smoking against lung function impairment. Automobile spray paint companies should do regular health check up on their workers. More research involving larger numbers of samples should be conducted to determine risk factors associated with lung function in automobile spray paint workers.